PENINGKATAN KOMPETENSI GURU DALAM MENGEMBANGKAN RPP KURIKULUM 2013 REVISI 2017 MELALUI PENDAMPINGAN BERKELANJUTAN - ENI RINDARTI (Universitas Muhammadiyah Prof Dr Hamka, 2018)
This study aims to improve the competence of teachers in developing the implementation plan of learning (RPP) on Curriculum 2013 through